Ambient air pollutant PM10 and risk of pregnancy-induced hypertension in urban China - Xin Huang; Jie Qiu; Yaqun Zhang; Weitao Qiu; Xiaochun He; Yixuan Wang; Qingmei Sun; Nan Zhao; Hongmei Cui; Sufen Liu; Zhongfeng Tang; Ya Chen; et al. (Environmental Research Letters, 2015)
Background : The relationship between air borne particulate matter ≤10 μ m (PM _10 ) exposure and pregnancy-induced hypertension (PIH) is inconclusive. Few studies have been conducted, and fewer were conducted in areas with high levels of PM _10 . Methods : To examine the association between PM _10 and PIH by different exposure time windows during pregnancy, we analyzed data from a birth cohort study conducted in Lanzhou, China including 8 745 pregnant women with available information on air pollution during pregnancy. A total of 333 PIH cases (127 gestational hypertension (GH) and 206 preeclampsia (PE)) were identified. PM _10 daily average concentrations of each subject were calculated according to the distance between home/work addresses and monitor stations using an inverse-distance weighting approach. Results : Average PM _10 concentration over the duration of entire pregnancy was significantly associated with PIH (OR = 1.12, 95%CI: 1.02, 1.23 per 10 μ g m ^−3 increase), PE (OR = 1.16, 95%CI: 1.03, 1.30 per 10 μ g m ^−3 increase), late onset PE (OR = 1.17, 95% CI: 1.03, 1.32 per10 μ g m ^−3 increase), and severe PE (OR = 1.25, 95% CI: 1.06, 1.48 per 10 μ g m ^−3 increase). Average PM _10 during the first 12 gestational weeks was associated with the risk of GH (OR = 1.10, 95% CI: 1.00, 1.21 per 10 μ g m ^−3 increase), and PM _10 exposure before 20 gestational weeks was associated with the risk of severe PE (OR = 1.14, 95% CI: 1.01, 1.30 per 10 μ g m ^−3 increase). Conclusions : We found that high level exposure to ambient PM _10 during pregnancy was associated with an increased risk of PIH, GH and PE and that the strength of the association varied by timing of exposure during pregnancy.